Characterization of matrix transformation of complex uncertain sequences via expected value operator - Das, B.; Debnath, P.; Tripathy, B.C. (Carpathian Mathematical Publications, 2022)
The aim of this paper is to study the concept of matrix transformation between complex uncertain sequences in mean. The characterization of the matrix transformation has been made by applying the concept of convergence of complex uncertain series. Moreover, in this context, some well-known theorems of real sequence spaces have been established by considering complex uncertain sequence via expected value operator.